The effect of culturally-adapted health education interventions among culturally and linguistically diverse (CALD) patients with a chronic illness: A meta-analysis and descriptive systematic review. Issue 7 (July 2021) - Lambert, Sylvie; Schaffler, Jamie Lynn; Ould Brahim, Lydia; Belzile, Eric; Laizner, Andréa Maria; Folch, Nathalie; Rosenberg, Ellen; Maheu, Christine; Ciofani, Luisa; Dubois, Sylvie; Gélinas-Phaneuf, Elisa; Drouin, Susan; et al.
Highlights: Health education interventions are as effective in CALD as in non-CALD populations. Lay providers may be useful in providing culturally adapted lifestyle advice. Both HCPs and lay providers should deliver health education interventions. Core outcome sets for health education interventions should be developed. Abstract: Objective: To review the effectiveness of health education interventions adapted for culturally and linguistically diverse (CALD) populations with a chronic illness. Methods: A systematic review and meta-analysis were conducted. Eligible studies were identified across six databases. Data were extracted and intervention effect was summarized using standardized mean difference. If there were insufficient data for meta-analysis, a descriptive summary was included. Modifying effects of intervention format, length, intensity, provider, self-management skills taught, and behavioral change techniques (BCTs) utilized were examined. Results: 58 studies were reviewed and data were extracted for 36 outcomes. Most interventions used multiple modes of delivery and were facilitated by bilingual health care professionals (HCPs). On average, interventions included 5.19 self-management skills and 4.82 BCTs. Interventions were effective in reducing BMI, cholesterol, triglycerides, blood glucose, HbA1C, and depression, and in increasing knowledge. Effectiveness was influenced partly by provider, with HCPs favored over lay providers or paraprofessionals in increasing knowledge; however, the opposite was noted for HbA1c. Conclusions: Health education interventions are effective among CALD populations, particularly at improving objective, distal outcomes (e.g., anthropometric measures). These interventions may be equally effective in improving proximal patient-reported outcomes (PROs); however, diversity in PROs limited analyses. Practice implications: Core outcome sets (COS) are needed to further investigate and compare health education intervention effectiveness on PROs.